Mocking fakeness : Performance, phonetic aspiration and ethnic humour - Halonen, Mia; Pietikäinen, Sari (John Benjamins Publishing Co, 2017)
Phonetic resources, like dialects and accents, are used in ethnic humour to build up a recognisable character that pokes fun at the stereotypes associated with a particular identity, sometimes with critical and political undertones. In this article, we examine the manipulation of one such resource, aspiration, used in performing and mocking one such clichéd character, called the fake Sámi. This character has a contested history in Finnish tourism and marketing practices, and is embedded in a long-standing debate about who can use emblems of Sámi identity for economic purposes. Adopting a sociophonetic language regard and folk linguistics approaches (Preston 2010; Niedzielski & Preston 2003) we explore how “fakeness” is constructed phonetically by the actors performing “Fake Sámi” in an indigenous Sámi television comedy show during a period of intense political debate in Finland over the legal definition of the category of indigenous Sámi. By analysing the use of hyperbolic aspiration of a prominent feature of Lappish Finnish dialect, the non-initial syllable /h/-sound, we show how the fakeness is performed by evoking linguistic stereotypes of a Finnish Lappish dialect and a Finnish English accent by a deliberate misuse of aspiration: aspirating when standard phonemes in speech should not be aspirated and not aspirating when phonemes should be aspirated. We argue that this kind of deliberate ambivalence and misuse of phonetic resources is a phonetic resource for reflexive postmodern identity performances. peerReviewed